Increasing Adolescents’ Knowledge Regarding Juvenile Delinquency Using a Physical Activity Approach - Leandre, Alvin Diva; Octavia, Fadilah Nur; Amelia, Dessy (Tarqabin Nusantara Group, 2023)
Juvenile delinquency, if defined through the opinions of several psychologists, is simply:all acts that violate the rules, whether legal rules or local customs that apply withincertain areas of society (Karlina, 2020). The number of juvenile delinquents in Indonesia is always increasingamounting to 10.7% and these include cases of theft, murder, promiscuity and drugs (Hardin& Nidia, 2022). The implementation stage was carried out using the Talk-Show method to students regarding problemsjuvenile delinquency and the role of sport/physical activity as an effort to prevent juvenile delinquency. Based on the resultsPre-Post Test of 5 sub-topics covering the definition of adolescence, pre-marital sex, drugs, smoking, and physical activityobtained Pre-Test results, 71.14% of respondents answered correctly, and Post-Test 81.53% of respondents who hadanswered correctly. Through the data that has been mentioned, increasing knowledge regarding juvenile delinquency throughthe Talk-Show method experienced an increase of 10.39%. Efforts to increase knowledge of juvenile delinquencyThrough this Talk-Show method, it is hoped that it will be able to provide broad knowledge to teenagerssignificantly affects development and growth in adolescence both physically and psychologically.And with this socialization, it is hoped that it will be able to provide positive direction for shifting focus todelinquency that occurs in teenagers.